(untitled) (Politeja, 2020)
‘Expulsion from the East’ in German Post-memory Literature This paper analyses post-memory narratives concerning the loss of the eastern provinces of the Reich as well as the flight and expulsion of their German inhabitants as found in the novels of German writers born in the 1950s and 1960s: Hans-Ulrich Treichel’s ‘Der Verlorene’ (1998) and ‘Anatolin’ (2008), Reinhard Jirgl’s ‘Die Unvollendeten’ (2003) and Ulrike Draesner’s ‘Sieben Sprünge vom Rand der Welt’ (2014). These stories showing far-reaching consequences of the ‘expulsion from the East’ examine complex mechanisms through which traumatic knowledge about the past is handed down from generation to generation. Consequently, the paper focuses on how the German authors make use of motifs characterizing post-memory or post-traumatic discourse about mourning and loss, and the way the key figures of that discourse structure their texts.